The relationship between parity and age with the regularity of Antenatal Care (ANC) visits at BPM Dinda - Arsanah, Eli; Sari, Jusmala; Hidayati, Diah Ulfa (Institute Of Computer Science (IOCS), 2024)
Implementing Antenatal Care (ANC) is a critical step in monitoring and maintaining the health of pregnant women to prevent the risk of maternal and neonatal complications. The regularity of ANC visits has a significant impact on maternal and infant health. Identifying factors that influence the regularity of ANC visits is important for improving the maternal health service system. This study aims to determine the relationship between parity and age and the regularity of ANC visits. The research design used was a cross-sectional observational study to evaluate the relationship between parity, age, and regularity of ANC visits. The population and sample in this study were pregnant women who received ANC services at BPM Dinda during the research period. The research variables measured were parity, and maternal age as the independent variable, and regularity of ANC visits as the dependent variable. The results showed that pregnant women with higher parity had a higher level of regularity of ANC visits due to previous experience and awareness of the importance of prenatal care, while the age variable did not have a significant relationship with ANC visits.